An investigation of functional state of the kickboxing athlete respiratory system - Oleksandr Volodchenko (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to study of the functional state of the respiratory system of kickboxing athletes. Material & Methods: in study involved 17 athletes - members of the Kharkov region team, age (17,88±0,58) years. Anthropometric studies were carried out according to standard methods, determined: body weight, body length, vital capacity of the lungs. Assessment of physical development, the state of the respiratory system was made with the SPIROCOM program. Results: the physical development of athletes is rated as average and harmonious. An increase in the vital capacity of the lungs was almost doubled in comparison with the standard. A significant increase in actual tidal volume and minute volume of respiration was established in comparison with the proper values. A significant increase in expiration time, a predominance of individuals with a large expiratory volume. Conclusion: established increased functionality of the respiratory system, which is due to the specifics of training in this sportа.